Impact of reflex locomotion and the Bobath concept on clinical and biomolecular parameters in people with multiple sclerosis: study protocol for a randomized controlled trial - Abreu-Corrales, Aymara; Velasco, Ana; Cuesta-Gómez, Alicia; Sánchez-González, Juan Luis (Frontiers in Neurology, 2023)
Introduction Multiple sclerosis (MS) is a progressive disease with a fluctuating and unpredictable course that has no curative treatment at present. One of its main characteristics is the variety of signs and symptoms that produce a high percentage of patients who present alterations in balance and gait during the development of the disease, decreased muscle strength, spasticity, or decreased pimax. Rehabilitative therapy, especially physiotherapy, is the main course of the treatment of these alterations using reflex locomotion and the Bobath concept as a form of kinesitherapy that activates the preorganized circuits of the central nervous system. Objective The objective of this study is to evaluate the reflex locomotion and Bobath concept effects on balance, spasticity, reaction time, respiratory parameters, and lacrimal biomolecular markers. Methods and analysis This is a randomized controlled trial on the effectiveness of two neurorehabilitation techniques in patients with multiple sclerosis conducted at the University of Salamanca. The research will take place at the Faculty of Nursing and Physiotherapy, University of Salamanca. The study will be conducted from June 2023 to June 2024. The reflex locomotion group will receive individual sessions of therapy (n = 27), and the Bobath concept group (n = 27) will receive the same number of sessions. Both groups will receive two sessions per week for 12 months. The measurement variables will be the Berg Balance Scale, the Tardieu Scale, the Cognitfit Program, Maximum Inspiratory Pressure, and Lacrimal Biomarkers. Ethics and dissemination This study has been approved by the Ethics Committee of the University of Salamanca on March 2023 (ref: 896). Limitations The main limitations of this study are the selection and number of patients, the delay in implementing the therapy within the initially scheduled period, inadequate sample collection, and inadequate sample processing. Trial registration number ClinicalTrials.gov; identifier: NCT05558683.